2020
DOI: 10.3389/fnbeh.2020.00123
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Changes in Cortisol and Tympanic Temperature Lateralization During Food Deprivation Stress in Marmoset Monkeys

Abstract: Temporal information about food availability can be easily entrained, as in the case of fixed feeding routines of captive animals. A sudden unintentional or deliberate delay (e.g., food deprivation—FD) leads to frustration and psychological stress due to the loss of temporal predictability. How marmosets—an increasingly used small primate—process and respond to FD stress has not been previously assessed. Here we delayed the routine feeding of adult captive marmosets for 3 or 6 h. Blood cortisol concentration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…These asymmetries could also be investigated using IRT to assess emotional valence [44]. As with the tympanic membrane temperature, the eye temperature was interpreted in this study to reflect the brain temperature of the same side [142,143]. The mechanism of thermal lateralisation is not clear but it could be due to lateralised cerebral blood flow, sympathetic innervation or activation of corticosteroid receptors [140,141,44,144].…”
Section: Discussionmentioning
confidence: 99%
“…These asymmetries could also be investigated using IRT to assess emotional valence [44]. As with the tympanic membrane temperature, the eye temperature was interpreted in this study to reflect the brain temperature of the same side [142,143]. The mechanism of thermal lateralisation is not clear but it could be due to lateralised cerebral blood flow, sympathetic innervation or activation of corticosteroid receptors [140,141,44,144].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on whether this effect is more widespread in the hemisphere and, since glucocorticoids are associated with ageing [57,58], a cumulative effect of stress with ageing is a potential explanation for declining strength of left-hand preference. Additionally, it has been found in marmosets that stress caused by unexpected and longer-term food deprivation effects the blood flow to, and activity of, the right hemisphere more than the left hemisphere [59], which is consistent with a greater effect of ageing on the right-hemisphere control of left-hand use.…”
Section: Discussionmentioning
confidence: 53%
“…This flexibility means that laterally biased behavior can indicate conditions of acute and chronic stress. In fact, somewhat prolonged stress caused by deprivation of food has been shown to elevate the activity of the right hemisphere, as Pereira et al (75) found in marmosets by measuring tympanic membrane temperature. Such flexibility in lateralization could be utilized to develop strategies to alter the strength and direction of laterality, thereby altering the reactions of animals to specific conditions and events (76).…”
Section: Applying Knowledge Of Laterality To Welfarementioning
confidence: 82%